2010
DOI: 10.4236/jmmce.2010.98051
|View full text |Cite
|
Sign up to set email alerts
|

MRR Improvement in Sinking Electrical Discharge Machining: A Review

Abstract: Electrical discharge machining (EDM) is one of the earliest non-traditional machining processes. EDM process is based on thermoelectric energy between the workpiece and an electrode. Material removal rate (MRR) is an important performance measure in EDM process. Since long, EDM researchers have explored a number of ways to improve and optimize the MRR including some unique experimental concepts that depart from the traditional EDM sparking phenomenon. Despite a range of different approaches, all the research w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 79 publications
0
24
0
2
Order By: Relevance
“…Consequently, it generates no cutting force, in contrast to other conventional cutting methods. Because very little heat is generated either, it does not deform the cut surface, further reducing mechanical stresses and entirely eliminating vibration problems that can occur with other methods (such as fine wire abrasive cutting) [11].…”
Section: The Contour Methods Cutting Assumptionsmentioning
confidence: 99%
“…Consequently, it generates no cutting force, in contrast to other conventional cutting methods. Because very little heat is generated either, it does not deform the cut surface, further reducing mechanical stresses and entirely eliminating vibration problems that can occur with other methods (such as fine wire abrasive cutting) [11].…”
Section: The Contour Methods Cutting Assumptionsmentioning
confidence: 99%
“…Most researchers consider peak current and on-time separately rather than combining them when studying the workpiece material removal rate (MRR). Ojha et al (2010) wrote a comprehensive review of how MRR can be enhanced. The paper concluded that MRR improved with a higher gap voltage, peak current, and on-time.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature review it is observed that the ranges of the EDM process variables are too large and differs from actual practices carried out in Industrial tool room. [7,8,9] Therefore the paper incorporates the results obtained as per actual parametric setting followed by machinists on the die sink EDM practices. Machinability leads to improper surface textures due to lack of availability of surface roughness information.…”
Section: 1tool Room Requisite For Precision Machiningmentioning
confidence: 99%